La expresión musical y su incidencia en el desarrollo del aprendizaje de los niños y niñas del nivel 2 del centro de educación inicial Mundo de Ilusiones, de la parroquia Chillogallo, cantón Quito, provincia de Pichincha, período lectivo 2013-2014. Lineamientos alternativos - Sangucho Gordón, Rosario de Jesús (2014)
This thesis entitled "THE MUSICAL EXPRESSION AND ITS IMPACT ON TWO LEVEL EARLY EDUCATION CENTER CHILDREN LEARNING DEVELOPMENT OF “MUNDO DE ILUSIONES SCHOOL” CHILLOGALLO PARISH, QUITO, CANTON, PICHINCHA PROVINCE.PERIOD 2013 -2014 ". ALTERNATIVE GUIDELINES, it has been structured and developed in accordance with the Rules of Academic Board of the National University of Loja. The general objective that guided the research was: To show the importance of Musical and its impact on the two level early education center children learning development of “Mundo de Ilusiones School”.. The methods used for the preparation of this research work were: Scientist, Inductive, Deductive, Analytic-Synthetic, Description - Statistical Model wich that served effectively help to achieve the goal. The techniques and instruments used were: a survey of teachers Level 2 Early Education “Mundo de Ilusiones Scholl”, the Chillogallo parish, Canton Quito, to establish that activities used in Musical Expression daily work. And, Test of Basic Functions. Adaptation "Reea" applied to children to assess themselves learning. Teacher´s survey concluded that: 100% of teachers surveyed say they do the activities of Musical Expression in daily; and 50% play simple instruments sound and recognize objects. According to the results of the Test of Basic Functions Adaptation "Reea" was obtained that 76% of boys and girls has investigated positive variables with more than 50%, equivalent to a Satisfactory learning; 64% have negative variables between 0 and 25%, equivalent to 24% Satisfactory Learning presents positive variables between 0 and 25% Unsatisfactory learning equivalent to a 24% negative variables has more than 50%, equivalent to an Unsatisfactory Learning , 0% positive variables presents between 25 and 50% equivalent Unsatisfactory; and 12% have negative variables between 25 and 50% equivalent to Unsatisfactory.